PERAN PENGEMBANGAN PARIWISATA PANTAI TAPALO TERHADAP PENDAPATAN EKONOMI MASYARAKAT DESA GOTOWASI KECAMATAN MABA SELATAN KABUPATEN HALMAHERA TIMUR PROPINSI MALUKU UTARA - Rauf, Barhima; Purwanto, Antonius; Mumu, Rudy (Universitas Sam Ratulangi, 2020)
In general, tourism is seen as a sector that can encourage and increase development activities, open new businesses, open jobs and can increase people's income and local indigenous income, if it can be managed and developed to the maximum. Maluku Utara tourism is supported by the potential of natural conditions and cultural relics of the past such as cultural and ancient tourism, natural tourism, and marine tourism that can be developed.Seeing this, it is expected that the government's support and policies to develop facilities and infrastructure in order to attract more tourists visiting the East Halmahera regency, especially on tapalo beach in Gotowasi Village.The implementation of regional development is directed to accelerate the realization of community welfare through improving services, empowerment, and community roles, as well as improving regional competitiveness. The implementation of regional development concerns the affairs of choice in this case the tourism sector, covering government affairs that are manifestly existing and have the potential to improve the welfare of the community in accordance with the conditions, uniqueness, and potential advantages of the region concerned. Community participation in tourism development can benefit and benefit tourism development. The impact of tourism on the economy of the community in Gotowasi Village is quite significant because the presence of Tapalo beach management can improve and help the family economy of gotowasi villagers.Â Keywords: tourism, tourists, development